Impacts of Properties of Dielectric Materials on VIAs in Printed Circuit Boards - Shan, A.; Prakash, V. R. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Printed circuit boards, or PCBs, are essential parts of electronic devices because they provide the framework for connecting different electrical parts. Conductive paths called Vertical Interconnect Accesses (VIAs) link the various PCB layers and are essential for maintaining adequate power distribution and signal integrity. The performance and dependability of vias are greatly impacted by the dielectric material selection made for PCBs. The effects of parasitic capacitance, inductance, and impedance on the PCB layout are critical in high-frequency design. This study looks into the frequency domain analysis of VIAS on a PCB made of several types of dielectric materials. By investigating the insertion loss, return loss, and parasitic RLC, the impacts of various materials in the via on the PCB are examined. In this investigation, four dielectric materials are used. Ansys HFSS tool is used to run the simulations..